The improvement of knowledge and skill sofnursesinthe kangaroo mother care method for low Birth weight infants through counseling - Moriana Br Sembirin; Yuni Sufyanti Arief; Kristiawati Kristiawati (Pediomaternal Nursing Journal, 2016)
ntroduction :A baby's weight at birth is a strong indicator of maternal and newborn health and nutrition. One oftheproblems that oftenoccur inlow birth weight (LBW) infants is the instability of body temperature. Kangaroo Mother Care(KMC) is an effective way to keep the infants warm.This study aimsto investigate the improvement of knowledge andskills of nurses in the implementation of the Kangaroo Mother Care method in LBW through counseling inPerinatology Room at General District Hospital (RSUD) Ade M. Djoen Sintang. Methods :The design of this research waspre-experimental. The population in this study was nurses and midwives in Perinatology Room at RSUD Ade M. DjoenSintang. Total sampling technique was used with 15 respondents. The independent variable was counseling, while thedependent variable was knowledge and skills. The data were collected by questionnaires and observations. Theanalysis used was Wilcoxon signed rank test with significance level of p <0,05. Result :The results showed thatknowledge (p=0.001) meant there was an improvement of knowledge of nurses and midwives about Kangaroo MotherCare method by giving counseling. Skills (p=0.001) meant there was an improvement of skills about Kangaroo MotherCare method in nurses and midwives by giving counseling as well. Discussion :It could be concluded that there was animprovement of knowledge and skills in conducting Kangaroo Mother Care method in dealing with low birth weightinfants. Nurses should increase knowledge and skills in nursing management in LBW infants by attending thecounseling. Kangaroo care method should be implemented step-by-step completely and correctly, without missing orforgetting any part.